Author Correction: NT5C2 methylation regulatory interplay between DNMT1 and insulin receptor in type 2 diabetes - Yng‑Tay Chen (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.